THEORETICAL COMPUTATION OF A STRESS FIELD IN A CYLINDRICAL GLASS SPECIMEN - NORBERT KREČMER (Ceramics-Silikáty, 2011)
This work deals with the computation of the stress field generated in an infinitely high glass cylinder while cooling. The theory of structural relaxation is used in order to compute the heat capacity, the thermal expansion coefficient, and the viscosity. The relaxation of the stress components is solved in the frame of the Maxwell viscoelasticity model. The obtained results were verified by the sensitivity analysis and compared with some experimental data.